The influence of economic, technical, and social aspects on energy-associated CO2 emissions in Malaysia: An extended Kaya identity approach - Pui, Kiew Ling; Othman, Jamal (Elsevier, 2019)
The rapid global economic development over the past two decades has been accompanied by rising energy demand and CO2 emission rates. Understanding the driving forces of CO2 emissions is necessary for future energy planning and policy formulation. This paper examines the driving factors behind the increase in CO2 emissions in Malaysia with special focus on the manufacturing, electricity and transportation sectors. The paper extends the Kaya identity by incorporating energy mix, investment efficiency, capital-labor substitution, population-to-employment, urbanization rates, and per capita CO2, along with the standard variables including economic activity, economic structure, and energy intensity. The paper also evaluates if any macroeconomic instability (economic crisis) in the country has led to reduction in emission rates. The study utilizes the latest country data, covering the period 2002–2016. The result shows that, while economic activity is always associated with CO2 emissions, more efficient energy use would help restrain the rise in emission rates without hampering economic growth regardless of economic structure. Emission reduction targets in Malaysia should be reinforced with an appropriate economic restructuring that restrains the economic structure effect. Due to the extensive energy use in the transportation and electricity generation, future emission control should focus more on these sectors. © 2019 Elsevier Ltd